Cationic Polyethyleneimine (PEI)-Gold Nanocomposites Modulate Macrophage Activation and Reprogram Mouse Breast Triple-Negative MET-1 Tumor Immunological Microenvironment - Vladimir Mulens-Arias; Alba Nicolás-Boluda; Florent Carn; Florence Gazeau (MDPI AG, 2022)
Nanomedicines based on inorganic nanoparticles have grown in the last decades due to the nanosystems' versatility in the coating, tuneability, and physical and chemical properties. Nonetheless, concerns have been raised regarding the immunotropic profile of nanoparticles and how metallic nanoparticles affect the immune system. Cationic polymer nanoparticles are widely used for cell transfection and proved to exert an adjuvant immunomodulatory effect that improves the efficiency of conventional vaccines against infection or cancer. Likewise, gold nanoparticles (AuNPs) also exhibit diverse effects on immune response depending on size or coatings. Photothermal or photodynamic therapy, radiosensitization, and drug or gene delivery systems take advantage of the unique properties of AuNPs to deeply modify the tumoral ecosystem. However, the collective effects that AuNPs combined with cationic polymers might exert on their own in the tumor immunological microenvironment remain elusive. The purpose of this study was to analyze the triple-negative breast tumor immunological microenvironment upon intratumoral injection of polyethyleneimine (PEI)-AuNP nanocomposites (named AuPEI) and elucidate how it might affect future immunotherapeutic approaches based on this nanosystem. AuPEI nanocomposites were synthesized through a one-pot synthesis method with PEI as both a reducing and capping agent, resulting in fractal assemblies of about 10 nm AuNPs. AuPEI induced an inflammatory profile in vitro in the mouse macrophage-like cells RAW264.7 as determined by the secretion of TNF-α and CCL5 while the immunosuppressor IL-10 was not increased. However, in vivo in the mouse breast MET-1 tumor model, AuPEI nanocomposites shifted the immunological tumor microenvironment toward an M2 phenotype with an immunosuppressive profile as determined by the infiltration of PD-1-positive lymphocytes. This dichotomy in AuPEI nanocomposites in vitro and in vivo might be attributed to the highly complex tumor microenvironment and highlights the importance of testing the immunogenicity of nanomaterials in vitro and more importantly in vivo in relevant immunocompetent mouse tumor models to better elucidate any adverse or unexpected effect.